METHOD FOR IMPROVING ENERGY ASYNCHRONOUS MACHINE - Mishin, V.; Loot, M.; Makarevich, S.; Chuyenko, R. (Energy and Automation, 2016)
Combining means doubling the number of phases and internal capacitive reactive power compensation in asynchronous machine leads to active influence on quantitative indicators of the rotating magnetic field - one of the main actors and its principle of electromechanical energy conversion process. An asynchronous machine offset increased energy efficiency.